Factors associated with Chagas screening among immigrants from an endemic country in Madrid, Spain - Romay-Barja, María; Boquete, Teresa; Martinez, Obdulia; Benito, Agustin; Blasco-Hernández, Teresa (PloS one, 2020)
Approximately 120,000 people live with Chagas disease in Europe, 43% of whom are living in Spain. Early diagnosis and treatment are critical to improve outcomes for those living with Chagas, and also for the prevention of ongoing transmission. The decision to be tested for Chagas is affected by a range of factors. Studies have highlighted the need to consider the wider social determinants of healthcare seeking behaviour related to Chagas. In Madrid, 44% of Bolivians undergo Chagas screening, which is a higher rate than other European regions, but studies concerning the factors which determine testing have not been performed. This study aimed to assess, for a first time, the factors associated with screening for Chagas among Bolivians living in Madrid trying to help in developing strategies and health recommendations. This was a cross-sectional survey about knowledge of Chagas and practices of Bolivians living in Madrid, Spain. A structured questionnaire was administered to 376 participants regarding Chagas health-seeking behaviour. Determinants were assessed by multiple logistic regressions adjusted by sex. After adjusting for others variables and sex, the factors shown to be associated with Chagas screening were to have between 35 and 54 years of age; coming from a department with high prevalence of Chagas (OR 2.17 95% CI 0.99-4.76); received information about Chagas in Spain (OR 2.44 95% CI 1.32-4.51); and received any advice to do the test, especially if the advice came from a professional. Health authorities should coordinate and promote strategies addressed to diagnose and treat Chagas taking into account all factors associated with screening. Our study suggests that professional advice appears to be the cornerstone to encourage Bolivians to undergo Chagas screening in Madrid. It is time to change the burden of the decision of being screened from the patient to the doctor. Being diagnosed for Chagas needs to become an institutional strategy.